Spherical nanostructures with anchor layers
By constructing a high-affinity polymer anchor layer on the central part of the nanostructure, the problem of strong solubility of the nanostructure in the prior art is solved, and higher biocompatibility and drug delivery efficiency are achieved.
Patent Information
- Application Number
- JP2024550176
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-03-08
- Filing Date
- 2023-03-08
- Publication Date
- 2025-04-30
AI Technical Summary
In the prior art, silicone nanostructures have strong solubility in vivo and are difficult to use as biocompatible anchor layers, which limits the biocompatibility and drug delivery efficiency of metal or metal oxide nanoparticles.
A polyspherical nanostructure is adopted, with its central part composed of a specific polymer scaffold and coated with an anchor layer based on a high affinity polymer, which improves surface reactivity and biocompatibility through high cross-connection.
It improves the biocompatibility of the nanostructure and drug delivery efficiency, extends the half-life in the body, and enhances the targeting and stability of the drug.
Smart Images

Figure 2025513683000001_ABST
Abstract
Description
[Technical field]
[0001] The present disclosure relates to polymeric nanostructures that have use as precursors to nanostructures that have medicinal uses. [Background technology]
[0002] The gold standard of cancer treatment is surgery. When surgery alone is not curative, multimodality treatment plans including chemotherapy and radiation therapy are used. Currently, approximately half of all cancer patients are treated with radiation therapy, either alone or in combination with other treatments. Radiation delivered as an external beam offers a relatively simple and practical approach to cause radiation damage to tumors. Although the intensity, location, and timing of external radiation can be well controlled and adjusted, drawbacks associated with this technique include destruction of normal tissue in the path of the beam, as well as damage to tissue surrounding the tumor. The risk of damaging surrounding healthy tissues makes external radiation therapy inconvenient for tumors located deep within and adjacent to vital organs. Furthermore, high radiation doses are often required to penetrate the tissue. Moreover, external radiation therapy often requires patients to make daily visits to the hospital for extended periods of time to be effective.
[0003] Total body radiation therapy, in which radioactive material is injected into the bloodstream and delivered to the tumor, offers a solution to many of the above-mentioned drawbacks associated with external radiation therapy.
[0004] Recent advances in nanotechnology have led to the development of nanocarriers designed for cancer detection and screening, in vivo molecular and cellular imaging, and therapeutic drug delivery. However, despite the large number of publications on nanosized carriers for cancer therapeutics, relatively few have made it into clinical trials and only a handful have been approved by the FDA.
[0005] The rationale for the suitability of nanosized materials as tumor-targeting radiation carriers is related to the enhanced vascular permeability and retention (EPR) effect. The EPR effect is based on the fact that capillaries in healthy tissues are practically impermeable to molecules larger than 3-4 nm, while capillaries in rapidly growing tumor tissues are much leakier. In addition, solid tumors tend to lack functional lymphatic vessels. These features combine to limit the removal of extravasated nanomaterials from most solid tumors and lead to the accumulation of nanosized materials within the tumor. EPR-mediated drug targeting is commonly referred to as passive tumor targeting, since it relies exclusively on the pathological properties of the target tissue, i.e., increased leakiness and poor lymphatic drainage.
[0006] EP 2923712 A1 discloses nanostructures with a hydrodynamic diameter of 8-100 nm, which can be used for imaging and / or radiotherapy.
[0007] Nanostructures made from silica dissolve rapidly when exposed to an aqueous environment at concentrations below the solubility of silicic acid. Dissolution of silica nanostructures occurs via hydrolytic depolymerization of the silica network, releasing free silicic acid and small oligomers of silicic acid. Silica nanostructures typically dissolve within a few hours. This is especially true at low concentrations of nanostructures, such as those suitable for in vivo use of nanostructures.
[0008] Dipodal silanes have some of the Si-O-Si- linkages replaced by Si-X-Si- linkages, where -X- represents a non-hydrolyzable chemical linker, and therefore the hydrolytic depolymerization of polymer networks derived from dipodal silanes is slower than that of polymer networks in silica.
[0009] US Patent Application Publication No. 2014275574 discloses the use of dipodal silanes to form coatings of excellent hydrolytic stability on macroscopic objects.
[0010] US Patent Application Publication No. 2012145037 discloses the use of dipodal silanes in the production of coatings for glass objects. Summary of the Invention [Problem to be solved by the invention]
[0011] Nanoparticles coated with a silica shell are known. In most cases, the nanoparticles are metal or metal oxide nanoparticles. However, the usefulness of such a silica layer as an anchor layer for coating nanoparticles to make them biocompatible is limited due to the tendency of the anchor layer to dissolve in vivo. One objective of the present disclosure is to solve this problem. [Means for solving the problem]
[0012] According to a first aspect, the above and other objects are achieved in whole or at least in part by a composition as defined in claim 1. According to this claim, the above object is achieved by a plurality of spherical nanostructures, the plurality of spherical nanostructures having a dispersity between 1 and 1.8, each nanostructure comprising a central portion comprising a polymer backbone of monomer residues according to formula (II), TIFF2025513683000002.tif9170 In the formula, each R 1 and R 2 is independently selected from the group consisting of a negative charge and H, and each R 3 are independently selected from the group consisting of a negative charge, H, and a covalent bond to the polymer backbone, and at least three R 3 is a bond to the polymer backbone, and m is an integer from 1 to 5, the central portion of the nanostructure having a volume average hydrodynamic diameter of 10 nm to 90 nm, and an anchor layer surrounding the central portion, the anchor layer comprising a polymer of monomer residues according to formula (I), TIFF2025513683000003.tif9170, wherein each R is independently selected from the group consisting of a negative charge, H, and a covalent bond, at least two R are independently selected from the group consisting of a covalent bond to a monomer residue of the core portion and a covalent bond to a monomer residue of the anchor layer, "-" represents a covalent bond, and n is 1 or 2, and the anchor layer has a thickness of 1 to 5 nm.
[0013] Preferably, of the six groups capable of crosslinking in the monomer of the anchor layer, two to five form crosslinks, i.e., two to five R are independently selected from the group consisting of covalent bonds to the monomer residue of the core portion and covalent bonds to the monomer residue of the anchor layer.
[0014] Even more preferably, the three or four R are independently selected from the group consisting of a covalent bond to a monomer residue of the core portion and a covalent bond to a monomer residue of the anchor layer.
[0015] A high degree of crosslinking results in an anchor layer with a high density, thereby increasing the number of attachment points for the coating per surface area of the spherical nanostructures (also referred to as primed nanostructures, as described below). Thus, it is possible to produce coated nanostructures in which the coating is stably attached to the nanostructures, resulting in improved biocompatibility and plasma half-life of the nanostructures.
[0016] The anchor layer may comprise a homopolymer.
[0017] According to one embodiment, the anchor layer has a thickness of 1.1 to 2.5 nm, or 1.3 to 1.6 nm. The anchor layer may have a thickness of 1.2 to 2.0 nm, such as 1.3 to 1.8 nm, such as 1.4 to 1.6 nm, such as 1.5 nm. Such nanostructures have been demonstrated to be particularly stable under physiological conditions.
[0018] According to a further embodiment, the 2 to 5 R are selected from the group comprising a covalent bond to a monomer residue of the core portion and a covalent bond to a monomer residue of the anchor layer.
[0019] According to yet another embodiment, n is 1. Thus, a particularly suitable monomer of the anchor layer is (RO)3Si-(CH2)-Si(OR)3.
[0020] Such a monomer can be achieved by using the monomer bis(triethoxysilyl)methane in preparing the anchor layer.
[0021] According to one embodiment, m is 3. Such nanostructures can, for example, chelate radioisotopes and can be used for imaging, such as PET or SPECT imaging, as well as for the treatment of cancer.
[0022] According to a further embodiment, the nanostructure further comprises a coating, which can make the nanostructure more biocompatible. Preferably, the coating comprises hydrophilic groups. Such a coating is particularly biocompatible.
[0023] According to a specific embodiment, the coating comprises polyethylene glycol. Such coatings are particularly biocompatible and stable under physiological conditions. Polyethylene glycol is also referred to as "PEG." Multiple ethylene glycol units linked together may also be referred to as polyethylene glycol chains or PEG chains.
[0024] According to a second aspect of the present disclosure, there is provided a method for producing a plurality of spherical nanostructures according to the present disclosure, the method comprising: (1) have a volume average hydrodynamic diameter of 10 nm to 90 nm, each of which comprises a polymer backbone of monomer residues according to formula (II); TIFF2025513683000004.tif9170 In the formula, each R 1 and R 2is independently selected from the group consisting of a negative charge and H, and each R 3 are independently selected from the group consisting of a negative charge, H, and a covalent bond to the polymer backbone, and at least three R 3 is a bond to the polymer backbone, and m is an integer from 1 to 5; According to formula (III), TIFF2025513683000005.tif9170, R 1 , R 2 , R 3 , R 4 , R 5 , and R 6 is independently selected from the group consisting of lower alkyl and aryl, "-" represents a covalent bond, and n is 1 or 2; providing a mixture in a mixture of water and a water-miscible organic solvent, wherein the ratio of monomer residues of the precursor nanostructure to monomers according to formula (III) is from 1:0.5 to 1:20; (2) heating the mixture of step (1) to a temperature of from 20° C. to 150° C. for a period of from 1 to 24 hours; Includes.
[0025] Such methods have been shown to result in spherical nanostructures with an anchor layer thick enough to allow for the application of an appropriate amount of coating to the nanostructures. A sufficient amount of coating affects the plasma half-life of the nanostructures. If too little coating is present, the plasma half-life will be shortened.
[0026] The thickness of the anchor layer is influenced by the ratio of monomer residues of the precursor nanostructure to the monomer according to formula (III). The ratio of monomer residues of the precursor nanostructure to the monomer according to formula (III) can be from 1:1 to 1:10, such as from 1:2.5 to 1:7, such as from 1:3 to 1:5.
[0027] The precursor nanostructures may have a volume average hydrodynamic diameter of from 10 nm to 90 nm, such as from 12.5 to 50 nm, such as from 15 to 30 nm, such as from 20 to 25 nm.
[0028] According to one embodiment of the method, R 1 , R 2 , R 3 , R 4 , R 5 , and R 6 is independently selected from the group consisting of methyl and ethyl, and n is 1. Thus, a suitable monomer for preparing the anchor layer is bis(triethoxysilyl)methane.
[0029] According to a specific embodiment of the method, the ratio of monomer residues of the precursor nanostructure to monomer according to formula (III) is 1:0.5 to 1:7, and / or in step (2), the mixture of step (1) is heated to a temperature of 80°C to 150°C for a period of 2 to 6 hours.
[0030] Preferably, the ratio of monomer residues of the precursor nanostructure to the monomer according to formula (III) is 1:0.5 to 1:7, and in step (2), the mixture of step (1) is heated to a temperature of 80° C. to 150° C. for a period of 2 to 6 hours.
[0031] According to a third aspect of the present disclosure, there is provided a pharmaceutical composition comprising a plurality of spherical nanostructures according to the present disclosure, the nanostructures further comprising a coating. Preferably, the coating comprises a hydrophilic group, and even more preferably, the coating comprises polyethylene glycol. Such a pharmaceutical composition can be used to manufacture a pharmaceutical composition comprising nanostructures comprising a radioisotope. Furthermore, when comprising a radioisotope, the nanostructures can be used for imaging, such as PET and SPECT imaging, and / or for the treatment of cancer.
[0032] According to a fourth aspect of the present disclosure, there is provided a pharmaceutical composition for use in the treatment and / or imaging of cancer, the pharmaceutical composition comprising a plurality of spherical nanostructures, the nanostructures further comprising a coating, the spherical nanostructures further comprising a radioisotope. Preferably, the coating comprises a hydrophilic group, and even more preferably, the coating comprises polyethylene glycol.
[0033] According to a fifth aspect of the present disclosure, there is provided the use of a plurality of spherical nanostructures according to the present disclosure and / or a product of a method according to the present disclosure as an intermediate in the production of a plurality of coated spherical nanostructures.
[0034] According to a sixth aspect of the present disclosure, there is provided the use of a plurality of spherical nanostructures according to the present disclosure and / or a product of a method according to the present disclosure as an intermediate in the manufacture of a medicament.
[0035] According to a seventh aspect of the present disclosure, there is provided the use of a pharmaceutical composition according to the present disclosure as a carrier for a radioisotope.
[0036] Other objects, features, and advantages of the present disclosure will become apparent from the following detailed description, from the experimental data, and from the appended claims. It is noted that the present disclosure relates to all possible combinations of features.
[0037] In general, all terms used in the claims should be interpreted according to their ordinary meaning in the art, unless expressly stated otherwise herein. Any reference to "a / an / the [component, means, step, etc.]" should be interpreted in an open-ended manner as referring to at least one example of said component, means, step, etc., unless expressly stated otherwise. The steps of any method disclosed herein do not have to be performed in the exact order disclosed, unless expressly stated otherwise.
[0038] As used herein, the term "comprising" and variations of this term are not intended to exclude other additives, components, integers, or steps.
[0039] Definition of Terms As used herein, the term "nanostructure" refers to entities whose overall particle size is in the nano range, i.e., 100 nm or less. As used herein, the term excludes structures that typically have an inorganic core and an organic coating, often referred to as "core-shell nanoparticles" or simply "nanoparticles."
[0040] As used herein, the term "spherical" is intended to describe a shape whose minor axis is equal to or greater than half of its major axis, i.e., the length of the longest axis passing through the center (centre of gravity) of the structure is equal to or less than twice the length of the shortest axis passing through the same point. For a non-limiting illustration of this definition, see Figure 1.
[0041] As used herein, the term "spherical nanostructures" refers to nanostructures as discussed above that have an essentially spherical morphology or shape, which is meant to exclude shapes such as flakes, rods, tubes, toroids, chains, and ribbons.
[0042] As used herein, the term "hydrodynamic diameter" refers to the diameter of a hypothetical hard sphere diffusing at the same rate as the nanostructure in solution, i.e., the diameter of an equivalent hard sphere calculated from the diffusion coefficient according to the Stokes-Einstein equation. This term is also known as the "Stokes diameter" or "Stokes-Einstein diameter". Hydration and shape are included in the behavior of the sphere. The diffusion coefficient is then calculated from time-dependent light scattering data obtained, for example, by dynamic light scattering (DLS). Other technical methods for measuring the diffusion coefficient of nanostructures are known to those skilled in the art and may be used instead. In such cases, the measurements should be referenced against DLS measurements. As a comparison, bovine serum albumin has been measured to have a hydrodynamic diameter of 6.9 nm by DLS in saline (150 mM NaCl) at room temperature at pH 7. Depending on whether number average, volume average, or scattering intensity average is used, the calculated values may vary slightly. The volume average is generally the most useful since it indicates what the nanostructure particle size is throughout the material. The mean diameters referred to herein refer to the volume average, i.e. the volume average hydrodynamic diameter, measured in saline or 8% ethylene glycol in saline (vol / vol) at 25°C.
[0043] As used herein, the term "DLS" is an acronym for Dynamic Light Scattering, a particle size measurement technique, which may also be referred to as Photon Correlation Spectroscopy or Quasi-Elastic Light Scattering. DLS diameters given herein and in the claims, unless otherwise specified, refer to the average of the volume-weighted peaks of a sample measured at 25°C in an aqueous solution of ionic strength equivalent to 150 mM NaCl, also referred to as saline, or in 8% ethylene glycol (volume / volume) in saline. In other words, the hydrodynamic diameters specified herein refer to the average of the volume-weighted peaks of a sample measured by DLS at 25°C in an aqueous solution of ionic strength equivalent to 150 mM NaCl, also referred to as saline, or in 8% ethylene glycol (volume / volume) in saline.
[0044] As used herein, SEC-ELSD is an acronym for Size Exclusion Chromatography with Evaporative Light Scattering Detection.
[0045] As used herein, the term "ICP-OES" is an acronym for Inductively Coupled Plasma - Optical Emission Spectrometry. ICP-OES is a technique used to determine the elemental composition in a sample.
[0046] The term "dispersity" is used in situations where the term polydispersity was previously used. For most applications, it is important that the particle size distribution around the mean value is as narrow as possible, i.e., a low dispersity. For a sample with perfectly uniform particle size, the dispersity is 1; for a non-uniform sample, the dispersity is greater than 1. Dispersity can be calculated in different ways, M w / M n or equivalently, M v / M n As a ratio of M w is the weight average molecular weight, M n is the number average molecular weight, M v is the volume average molecular weight. In this specification, the inventors follow the recommendation by the International Union of Pure and Applied Chemistry (Pure Appl. Chem., Vol. 81, No. 2, pp. 351-353, 2009. doi:10.1351 / PAC-REC-08-05-02) to determine the degree of dispersion of the nanostructure sample. Similarly, TIFF2025513683000006.tif7170 tif6170, dv is the volume mean diameter as measured by DLS, and d nis the number average diameter as measured by DLS. Another way to express the dispersity of a material is to compare it to a known particle size standard. As a non-limiting example illustrated here, a suitable particle size standard could be bovine serum albumin (BSA), or thyroglobulin, or empty cowpea mosaic virus (CPMV) VLPs.
[0047] As used herein, the term "molecular weight" refers to the molecular weight of a compound having a specific molecular structure, or the weight-average molecular weight, also called mass-average molar mass or weight-average molar mass, of a compound that contains a polymeric portion, and the number of monomers of the polymeric portion varies between different individual molecules.Thus, the molecular weight of a compound having a specific molecular structure is the molecular weight calculated based on the number and nature of atoms of the compound, or the molecular weight measured, for example, by mass spectrometry.The molecular weight of a compound that contains a polymeric portion refers to the weight-average molecular weight, also called mass-average molar mass or weight-average molar mass, which can be determined, for example, by gel filtration chromatography or size exclusion chromatography (SEC). More specifically, the weight average molecular weight may be determined according to ISO 16014-1:2019 and ISO 16014-5:2019 ("Determination of average molecular weight and molecular weight distribution of polymers using size-exclusion chromatography"), or according to ISO 16014-1:2019 in combination with any of ISO 16014-2:2019 through ISO 16014-4:2019. Alternatively, the weight average molecular weight may be determined by SEC and confirmed using liquid chromatography-mass spectrometry (LC-MS) or high performance liquid chromatography (HPLC).
[0048] A "monomer" is a molecule that can be covalently linked to other molecules of the same type (and, if desired, other types of molecules) to form polymers, i.e., macromolecules composed of multiple monomer residues.
[0049] The term "monomer residue" refers to the atoms from one monomer unit that has been incorporated into a larger polymer. Depending on how the monomers are linked, all of the atoms may be retained or some may be lost during bond formation.
[0050] By "crosslinking" we mean the connection between two different chains in a polymer. It is usually formed by the reaction of a multifunctional monomer (i.e., a crosslinker) that is added during the formation of the polymer. Crosslinks can also be introduced, for example, by radiation treatment, chemical means, or heat. For the materials of the present disclosure, which are network polymers of monomers with multiple branching capabilities, the usual expression of crosslinking degree becomes somewhat inappropriate. For simplicity, we only describe the average number of bonds between monomers. For example, if a monomer can form six bonds with other molecules, and on average three of them are filled, we avoid the term crosslinking degree and describe that there are "on average three bonds with other monomers," or sometimes "on average three bonds out of six possible with other monomers."
[0051] The term "crosslinked" refers to the structure formed after at least one crosslink has been formed.
[0052] As used herein, the term "polymer backbone" refers to a covalently bonded group of atoms that forms a network structure with multiple crosslinks. Such a polymer backbone is formed by linking suitable monomers and / or oligomers (i.e., molecular complexes consisting of several monomer residues) through covalent bonds. Some examples of monomers include styrene, propylene, ethylene, tetrafluoroethylene, trifluoroethylene, difluoroethylene, methyl acrylate, ethyl acrylate, hydroxyethyl acrylate, acrylamide, methyl methacrylate, ethyl methacrylate, hydroxyethyl methacrylate, H2N-(CH2) p-COOH (p is 1-10), 3-aminobenzoic acid, 4-aminobenzoic acid, N-vinylpyrrolidone, and silicone precursors such as (CH3COO)2Si(CH3)2. Some examples of polymer backbones are terephthalic acid + 1,4 diaminobenzene, terephthalic acid + ethylene glycol, and HCOO-(CH2). p COOH+H2N-(CH2) q It is formed from a corresponding pair of monomers such as -NH2 (p and q are independently 1 to 10). Oligomers having 2 to 10 linked monomer units can be used as precursors. Some examples of oligomers that are different from the linked groups of monomers listed above are cyclic or polycyclic silanes such as hexamethylcyclotrisiloxane, 2,4,6,8-tetramethylcyclotetrasiloxane, and decamethylcyclopentasiloxane. Some examples of crosslinkers are N,N'-methylenebis(acrylamide), O,O'-methylenebis(acrylic acid), epichlorohydrin, divinylbenzene, 1,3-divinyltetramethyldisiloxane, 1,3-phenylene diisocyanate, 3,3''-biphenyltetracarboxylic dianhydride, 1,4-butanediol divinyl ether, tetraethoxysilane, oligosilicates such as metasilicates or silsequioxanes, organosilanes such as bis(triethoxysilyl)methane, bis(triethoxysilyl)ethane, bis(triethoxysilyl)propane, bis(triethoxysilyl)butane, methyltriethoxysilane, ethyltriethoxysilane, and propyltriethoxysilane.
[0053] The polymer backbone constitutes the backbone of the central portion of the nanostructure. One skilled in the art will appreciate that the random nature of the polymerization process will result in materials with many similar, but often not identical, mixtures of branching patterns, crosslinking locations, and molecular weights.
[0054] The term "chelating group" refers to a chemical group that can compete well with water for electrostatic binding of a positively charged ion. A single chelating group does not bind very strongly, but when multiple chelating groups surround a positively charged ion, a synergistic binding enhancement occurs. This is called chelation.
[0055] As used herein, the terms "covalently attached," "covalently linked," and "covalently bound" are synonymous and have the meaning known to those of skill in the art.
[0056] As used herein, the term "independently selected" means that each of the different components mentioned preceding the term is selected from the group that follows the term independently or separately from the selection of the other mentioned components.
[0057] The term "geminal bisphosphonate group" refers to two phosphonate groups separated by one carbon atom, i.e., the phosphonate groups are attached to the same carbon atom. Compounds containing such geminal bisphosphonate groups are often referred to as 1,1-bisphosphonates (or 1,1-diphosphonates). The phosphonate group in the geminal bisphosphonate group may be substituted.
[0058] The term "radionuclide" means an unstable form of a chemical element that undergoes radioactive decay resulting in the emission of alpha, beta, and / or gamma rays.
[0059] As used herein, the expression "radionuclide for imaging and / or radiotherapy" refers to actinium-225 ( 225 Ac), copper-62( 62 Cu), Copper-64( 64 Cu), Copper-67( 67 Cu), Gallium-67( 67 Ga), Gallium-68( 68 Ga), Holmium-166( 166 Ho), Indium-111 ( 111 In), Pb-212(212 Pb), Lutetium-177( 177 Lu), Radium-223 ( 223 Ra), Rhenium-186( 186 Re), rhenium-188( 188 Re), Rubidium-82 ( 82 Rb), Samarium-153( 153 Sm), Strontium-89 ( 89 Sr), Technetium-99m ( 99m Tc 3+ ), Thallium-201( 201 Tl), thorium-227( 227 Th), Yttrium-86( 86 Y), Yttrium-90 ( 90 Y), and zirconium-89 ( 89 The expression "radionuclide for imaging and / or radiotherapy" also encompasses combinations of two or more of the abovementioned radionuclides.
[0060] As used herein, the expression "radionuclide for imaging" refers to copper-62 ( 62 Cu), Copper-67( 67 Cu), Gallium-67( 67 Ga), Gallium-68( 68 Ga), Indium-111 ( 111 In), Lutetium-177( 177 Lu), Rhenium-186( 186 Re), Rubidium-82 ( 82 Rb), Technetium-99m ( 99m Tc 3+ ), Thallium-201( 201 Tl), Yttrium-86( 86 Y), and zirconium-89 ( 89 The expression "radionuclide for imaging" also encompasses combinations of two or more of the abovementioned radionuclides.
[0061] As used herein, the expression "radionuclide for PET imaging" refers to copper-62 ( 62 Cu), Gallium-68(68 Ga), Rubidium-82( 82 Rb), Yttrium-86( 86 Y), and zirconium-89 ( 89 The expression "radionuclide for PET imaging" also encompasses combinations of two or more of the abovementioned radionuclides.
[0062] As used herein, the expression "radionuclide for SPECT imaging" refers to gallium-67 ( 67 Ga), Indium-111 ( 111 In), Technetium-99m ( 99m Tc 3+ ), Lutetium-177( 177 Lu), and Thallium-201 ( 201 Tl). The expression "radionuclide for SPECT imaging" also encompasses combinations of two or more of the abovementioned radionuclides.
[0063] As used herein, the expression "radionuclide for radiotherapy" refers to actinium-225 ( 225 Ac), Copper-64( 64 Cu), Copper-67( 67 Cu), Holmium-166( 166 Ho), lead-212( 212 Pb), Lutetium-177( 177 Lu), Radium-223 ( 223 Ra), Rhenium-186( 186 Re), rhenium-188( 188 Re), Samarium-153( 153 Sm), Strontium-89 ( 89 Sr), Thorium-227( 227 Th), and Yttrium-90 ( 90 The expression "radionuclide for radiotherapy" also encompasses combinations of two or more of the abovementioned radionuclides.
[0064] As used herein, the expression "radionuclide for PET imaging and radiotherapy" refers to actinium-225 (225 Ac), copper-62( 62 Cu), Copper-64( 64 Cu), Copper-67( 67 Cu), Gallium-68( 68 Ga), Holmium-166( 166 Ho), lead-212( 212 Pb), Lutetium-177( 177 Lu), Radium-223 ( 223 Ra), Rhenium-186( 186 Re), rhenium-188( 188 Re), Rubidium-82 ( 82 Rb), Samarium-153( 153 Sm), Strontium-89 ( 89 Sr), Thorium-227( 227 Th), Yttrium-90( 90 Y), and zirconium-89 ( 89 The expression "radionuclide for PET imaging and radiotherapy" also encompasses combinations of two or more of the abovementioned radionuclides.
[0065] As used herein, the expression "radionuclide for SPECT imaging and radiotherapy" refers to actinium-225 ( 225 Ac), Copper-64( 64 Cu), Copper-67( 67 Cu), Gallium-67( 67 Ga), Holmium-166( 166 Ho), Indium-111 ( 111 In), Pb-212( 212 Pb), Lutetium-177( 177 Lu), Radium-223 ( 223 Ra), Rhenium-186( 186 Re), rhenium-188( 188 Re), Samarium-153( 153 Sm), Strontium-89 ( 89 Sr), Technetium-99m ( 99m Tc 3+ ), Thallium-201( 201 Tl), thorium-227( 227Th), and Yttrium-90 ( 90 The expression "radionuclide for SPECT imaging and radiotherapy" also encompasses a combination of two or more of the abovementioned radionuclides.
[0066] As used herein, the term "oxysilane" refers to any compound in which one or more oxygen atoms are bonded to a silicon atom. Non-limiting examples include: The file is TIFF2025513683000008.tif34170.
[0067] As used herein, the term "organosilane" means an organic compound that contains one or more carbon-silicon bonds.
[0068] As used herein, the term "alkoxysilane" means any compound that contains one or more carbon-oxygen-silicon moieties.
[0069] The terms "hydrocarbon" and "hydrocarbon chain" are used herein to denote an organic residue composed of hydrogen and carbon. A hydrocarbon may be fully saturated or may contain one or more unsaturations. A hydrocarbon according to the present disclosure may contain any number of carbon atoms from 1 to 50.
[0070] As used herein, the term "alkyl" refers to a straight or branched chain, fully saturated (no double or triple bonds) hydrocarbon group. As used herein, an alkyl group can have 1 to 15 carbon atoms. Typical alkyl groups include, but are in no way limited to, methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tertiary butyl, pentyl, hexyl, and the like.
[0071] As used herein, the term "lower alkyl" means an alkyl having 1 to 8 carbon atoms.
[0072] As used herein, the term "lower alcohol" means an alcohol having from 1 to 8 carbon atoms.
[0073] Numeric ranges: whenever used herein, unless otherwise specified, a numerical range such as "1 to 8" or "1-8" refers to each integer within the given range, for example, "1 to 8 carbon atoms" and "1-8 carbon atoms" means that an alkyl group may consist of 1 carbon atom, 2 carbon atoms, 3 carbon atoms, etc., up to 8 carbon atoms. However, there are some exceptions that will be apparent to those skilled in the art. In particular, whenever a range is given herein for a molar ratio, such as the Si / P molar ratio, diameter or particle size, pH, duration, concentration, osmolality, or temperature of a nanostructure, the range includes all decimals within the range, including the upper and lower limits.
[0074] As used herein, the term "alkoxy" refers to the formula -OR, where R is lower alkyl, such as methoxy, ethoxy, n-propoxy, 1-methylethoxy (isopropoxy), n-butoxy, iso-butoxy, sec-butoxy, tert-butoxy, amyloxy, iso-amyloxy, etc. Alkoxy groups in accordance with the present disclosure may be optionally substituted.
[0075] As used herein, the term "aryl" refers to a carbocyclic (i.e., all carbon) ring or two or more fused rings (i.e., rings sharing two adjacent carbon atoms) having a completely delocalized pi-electron system. Examples of aryl groups include, but are not limited to, benzene, naphthalene, and azulene. Aryl groups according to the present disclosure may be optionally substituted, such as, for example, phenoxy, naphthalenyloxy, azulenyloxy, anthracenyloxy, naphthalenylthio, phenylthio, and the like. Aryloxy may be optionally substituted.
[0076] As used herein, the term "acyl" refers to the functional group RC(=O)--, where R is an organic residue.
[0077] As used herein, the term "coated nanostructures" (or nanostructures having a coating) is used to describe materials that can be produced from the nanostructures of the present disclosure by the addition of one or more layers of additional materials. Often, such coated nanostructures are intended for use in radioisotope therapy.
[0078] As used herein, the term "dipodal silane" refers to an organosilane that contains two silicon atoms linked by a non-hydrolyzable or essentially non-hydrolyzable linker, where each silicon atom is further substituted such that the silicon atoms can react independently to form bonds to a siloxane network and / or can be part of such a network.
[0079] As used herein, the terms "siloxane bond," "siloxane linkage," and "siloxane network" refer to moieties that contain Si-O-Si.
[0080] As used herein, the term "priming" refers to a material that is applied to another material, object, surface, substrate, interface, or structure to aid, improve, promote, enable, stabilize, or enhance the adhesion of, connection with, spreading of, wetting by, reaction with, bonding to, surface coverage by, or integration with a third material. Primer can be used as a verb meaning to apply a primer (material) (to something) or as the name of the process of applying a primer. It is generally clear to one skilled in the art which form of the term "priming" is used. A material, object, surface, substrate, interface, or structure that has been primed is said to be primed.
[0081] Thus, the term "primed nanostructure" is used to describe a core nanostructure surrounded by an anchor layer as described below.
[0082] As used herein, the term "coating" refers to a layer of material applied to a surface to impart one or more properties to the surface. Often, the coating is covalently attached to the surface. Often, the surface is a nanostructured surface. Often, the properties imparted to the surface include inertness, such as bioinertness. The term "coating" can also refer to the process of applying a coating to a surface, and the term "coat" can be used as a verb meaning "to apply a coating to." It will generally be clear to one of ordinary skill in the art which form of the term "coating" is to be used in a particular case.
[0083] BTESM is used as an abbreviation for bis(triethoxysilyl)methane.
[0084] BTESE is used as an abbreviation for bis(triethoxysilyl)ethane.
[0085] As used herein, the term "Tris" means tris(hydroxymethyl)aminomethane.
[0086] As used herein, the terms "vol / vol" or "v / v" stand for volume / volume.
[0087] As used herein, 90.0% (vol / vol) aqueous ethylene glycol means a mixture of 90.0% (vol / vol) ethylene glycol and 10.0% (vol / vol) water.
[0088] As used herein, the term "w / w" stands for weight / weight.
[0089] By way of example, embodiments of the present teachings will now be described with reference to the accompanying drawings, in which: [Brief description of the drawings]
[0090] [Figure 1] FIG. 1 is an explanatory diagram of a spherical shape. [Diagram 2] FIG. 2 is an illustration of the core portion, anchor layer, and coated nanostructures. [Diagram 3] FIG. 3 is a scheme of the manufacturing process. [Figure 4] FIG. 4 shows the 1H-NMR spectra of the precursor nanostructures (top chart) and the primed spherical nanostructures (bottom chart). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0091] Briefly, nanostructures according to the present disclosure have a central portion comprising a first type of polymer and a reactive layer of a different type of polymer ("anchor layer") on the surface of the central portion. Such nanostructures that include both a central portion and an anchor layer are referred to as "primed nanostructures," and nanostructures without an anchor layer, i.e., only a central portion, are referred to as "precursor nanostructures."
[0092] The reactive layer, or "anchor layer", has the purpose of making the primed nanostructure reactive or more reactive towards derivatization with other materials, hereafter referred to as "coating precursors". The anchor layer increases the surface density of groups suitable for reaction with the coating precursor on the nanostructure surface compared to the central portion without the anchor layer. After reaction with the reactive groups of the anchor layer, the coating precursor forms a coating on the original nanostructure. The primed nanostructure, i.e., the nanostructure comprising the central portion surrounded by the anchor layer and the coating, is referred to herein as the "coated nanostructure". For a drawing illustration, see FIG. 2.
[0093] Figure 2 is a schematic diagram of a nanostructure as described herein. The various components of the nanostructure are described in detail below. In addition, specific characteristics of the various components are also discussed.
[0094] Figure 2A shows the mean hydrodynamic diameter, D A Such nanostructures are also referred to as "precursor nanostructures."
[0095] FIG. 2B shows a nanostructure according to the present disclosure, including a "center portion" and an "anchor layer." Such nanostructures are also referred to as "primed nanostructures." Such nanostructures have an average hydrodynamic diameter, D B Therefore, the thickness of the anchor layer can be calculated as half the difference between the hydrodynamic diameter of the primed nanostructure and the hydrodynamic diameter of the precursor nanostructure. This is expressed as (D B -D A ) / 2.
[0096] FIG. 2C shows a nanostructure according to the present disclosure, including a "core portion," an "anchor layer," and a "coating." Such nanostructures are also referred to as "coated nanostructures." Such nanostructures have an average hydrodynamic diameter, D C Therefore, the thickness of the "coating" is (D C -D B ) / 2.
[0097] Primed nanostructures A composition comprising primed nanostructures according to the present disclosure will always comprise a plurality of said primed nanostructures, the plurality of spherical nanostructures being characterized by a statistical measure such as, but not limited to, a particle size measure such as average hydrodynamic diameter, average molecular weight, dispersity, density, concentration, or percentage passing through a particular calibrated filter having a nominal cutoff value for molecular weight.
[0098] Specifically, the plurality of spherical nanostructures according to the present disclosure include primed nanostructures in which the anchor layer comprises a crosslinked polymer network, which may be a homopolymer of a single monomer or a copolymer of two or more different monomers.
[0099] The primed nanostructures are typically prepared and / or used as a solution, typically an aqueous solution.
[0100] The central part (the "precursor nanostructure") The mean hydrodynamic diameter of the central part is D in Fig. 2. A is equivalent to.
[0101] Typically the central portion has an average hydrodynamic diameter of 10 to 90 nm, such as 12 to 85 nm, such as 15 to 30 nm, such as 20 to 25 nm.
[0102] In one embodiment, the central portion has an average hydrodynamic diameter of from 10 to 25 nm, such as from 15 to 20 nm.
[0103] Preferably, the central moiety comprises a chelating group, such as a geminal bisphosphonate.
[0104] Preferably, the central moiety comprises a geminal bisphosphonate and an organosilane.
[0105] Preferably, the central moiety comprises a polymeric backbone of monomer residues according to formula (II): TIFF2025513683000009.tif9170, each R 1 and R 2 is independently selected from the group consisting of a negative charge and H, and each R 3 are independently selected from the group consisting of a negative charge, H, and a covalent bond to the polymer backbone, and at least three R 3 is the bond to the polymer backbone and m is an integer from 1 to 5.
[0106] Anchor Layer The thickness of the anchor layer affects the hydrolytic stability and plasma half-life of the nanostructures in vivo. Nanostructures with anchor layers that are too thin, typically less than 1 nm, have shorter plasma half-lives than nanostructures with anchor layers greater than 1 nm (see Example 9). Thus, nanostructures with anchor layers that are too thin are less good for use as precursors to coated nanostructures that are to be used in vivo as described below.
[0107] The thickness of the anchor layer is 1 to 5 nm.
[0108] In one embodiment, the thickness of the anchor layer is from 1.1 to 2.5 nm, such as from 1.2 to 2 nm, such as from 1.3 to 1.6 nm, such as from 1.4 to 1.5 nm.
[0109] The degree of crosslinking of the polymer of the anchor layer is exceptionally high for a random polymer, such as on average more than 2 bonds per monomer, or more than 3 bonds per monomer. Even higher degrees of crosslinking, such as 4-5, may be contemplated in some polymer backbones according to the present disclosure.
[0110] It is clear to those skilled in the art that even if a monomer with crosslinking or branching potential is used as a monomer for producing the central part, not all of its potential is utilized, but residual groups with crosslinking potential are left behind to react with the precursors of the anchor layer. Thus, in the nanostructures according to the present disclosure, the anchor layer is covalently bonded to the central part.
[0111] In one embodiment, the degree of crosslinking achieved in the anchor layer is, on average, 3-5 bonds per monomer.
[0112] In another embodiment, the anchor layer comprises a homopolymer.
[0113] Preferably, between 2 and 5 of the 6 groups with crosslinking potential in the monomer actually form crosslinks.
[0114] A high degree of crosslinking results in a denser anchor layer. A high degree of crosslinking can be achieved by the methods disclosed below. In Example 12, the density of the anchor layer (1.9 g / cm 3 ) is higher than most organic solids, but the bulk density of amorphous silica (2.65 g / cm 3 , https: / / en.wikipedia.org / wiki / Silicon_dioxide). The atomic density of silica, assuming pure SiO2, is 80 atoms / nm 3 In the anchor layer, where CH2 instead of oxygen connects a pair of silicon atoms, the atomic density in the anchor layer is close to that (77 non-hydrogen atoms / nm2) when there are an average of four bonds to other monomer residues. 3 ) The density evaluation is described in Example 12. According to the present disclosure, bis(trialkoxysilyl)alkanes are used to form the anchor layer of the nanostructures. Thus, the anchor layer comprises a polymer of monomer residues according to formula (I): TIFF2025513683000010.tif9170In the formula, each R is independently selected from the group consisting of a negative charge, H, and a covalent bond, at least two R are independently selected from the group consisting of a covalent bond to a monomer residue of the core portion and a covalent bond to a monomer residue of the anchor layer, "-" represents a covalent bond, and n is 1 or 2.
[0115] Preferably, the 2 to 5 R are selected from the group comprising covalent bonds to monomer residues of the central moiety and covalent bonds to monomer residues of the anchor layer. Thus, as described above, the anchor layer may comprise a homopolymer of monomer residues according to formula (I) in which 2 to 5 R, preferably 3 or 4 R, form covalent bonds to either other monomers or the central moiety of the anchor layer.
[0116] The alkoxysilanes are separated by 1 or 2 carbon atoms, i.e., n is 1 or 2. Preferably, n is 1.
[0117] A particularly suitable monomer for the anchor layer is bis(triethoxysilyl)methane (see Example 1B). Nanostructures with such an anchor layer have been shown to have a plasma half-life of 12 hours (see Examples 4 and 9).
[0118] If desired, other functional groups may be present on one or more of the carbon atoms between the silanes.
[0119] Typically, the anchor layer serves as an attachment layer for an additional polymer layer, referred to as a “coating” or “coating layer.” The coating (discussed in more detail below) may, among other things, improve the biocompatibility of the nanostructures.
[0120] The primed nanostructure anchor layer allows for a higher coating density than coating directly onto the precursor nanostructures. Insufficient coating density can result in nanostructures with less suspension stability, which can cause aggregation and / or precipitation of the nanostructures under conditions where more densely coated nanostructures would remain in solution without agglomeration (see Example 7).
[0121] Another advantage of the primed nanostructures is their stability against degradation: they are significantly more stable in hydrolytic environments, such as in pharmaceutical formulations or in vivo, than nanostructures with coatings formed directly on the precursor nanostructures. This is shown in Examples 8 and 9 for aqueous and in vivo experiments, respectively.
[0122] Example 20 provides a further example of more stable attachment of coatings to nanostructures having an anchor layer according to the present disclosure compared to nanostructures without an anchor layer. Example 19B, a coating derived from a coating precursor capable of bonding to nanostructures through a single silicon atom, and Examples 4 and 14, coatings derived from coating precursors capable of bonding to nanostructures through two silicon atoms, all stably bond to the nanostructures when coated onto precursor nanostructures having an anchor layer according to the present disclosure.
[0123] To demonstrate that the anchor layer according to the present disclosure is superior to well-established methods, a material was prepared where a coating layer was applied to a nanostructure in which the anchor layer was amorphous silica derived from tetraethyl orthosilicate (see Example 6), and in Examples 8 and 9, this material is shown to be less stable in aqueous solution and in vivo compared to nanostructures having an anchor layer according to the present disclosure.
[0124] To further illustrate that nanostructures with anchor layers according to the present disclosure are superior to well-established methods, different nanostructures were evaluated in an accelerated aging test (Example 20). Four different PEG-coated nanostructures were tested: A-PEG-coated nanostructures with a central portion according to the present disclosure and an anchor layer derived from BTESM (i.e., n=1) according to the present disclosure (Example 4); B-PEG-coated nanostructures with a central portion according to the present disclosure and an anchor layer derived from BTESE (i.e., n=2) according to the present disclosure (Example 14); C-PEG-coated nanostructures with a central portion synthesized according to Example 1c of US Patent Application Publication No. 2017 / 0106105(A1) (no anchor layer according to the present disclosure) (Example 18); and D-PEG-coated nanostructures with a central portion synthesized according to Example 1c of US Patent Application Publication No. 2017 / 0106105(A1) and an anchor layer derived from BTESM (i.e., n=1) according to the present disclosure (Example 19B). The results shown in Table 2 demonstrate that when the coated nanostructures also have an anchor layer according to the present disclosure (A, B, and D), the hydrolytic stability of the coating is improved compared to the coated nanostructure without the anchor layer (C). Furthermore, the coated nanostructures having both a central portion according to the present disclosure and an anchor layer according to the present disclosure (A and B) are more hydrolytically stable than the nanostructure having a central portion synthesized according to Example 1c of U.S. Patent Application Publication No. 2017 / 0106105 A1 and an anchor layer according to the present disclosure (D).
[0125] Specific Embodiments of Primed Nanostructures In one embodiment, the central portion has a diameter of 10 to 90 nm and the anchor layer is 1 to 5 nm.
[0126] In one embodiment, the central portion has a diameter of 10 to 85 nm and the anchor layer is 1 to 5 nm.
[0127] In another embodiment, the central portion has a diameter of 10 to 25 nm and the anchor layer is 1 to 2.5 nm.
[0128] In yet another embodiment, the central portion has a diameter of 15-20 nm and the anchor layer is 1-2 nm.
[0129] In a further embodiment, the central portion has a diameter of 15 to 20 nm and the anchor layer is 1.3 to 1.6 nm.
[0130] In yet another embodiment, the dispersity of the nanostructures is less than 1.35.
[0131] In one embodiment, the dispersity of the nanostructures is less than 1.25.
[0132] The precursor nanostructures were synthesized by polycondensation of monomers containing geminal bisphosphonates and organosilanes.
[0133] In particular, the central portion, i.e. the precursor nanostructure, comprises a polymeric backbone of monomer residues according to formula (II): TIFF2025513683000011.tif9170 In the formula, each R 1 and R 2 is independently selected from the group consisting of a negative charge and H, and each R 3 are independently selected from the group consisting of a negative charge, H, and a covalent bond to the polymer backbone, and at least three R 3 is the bond to the polymer backbone, and m is an integer from 1 to 5. Preferably, m is 3.
[0134] The anchor layer surrounding the central portion comprises a polymer of monomer residues according to formula (I): In the formula TIFF2025513683000012.tif9170, each R is independently selected from the group consisting of a negative charge, H, and a covalent bond, at least two R, preferably three to four, are independently selected from the group consisting of a covalent bond to a monomer residue of the central portion and a covalent bond to a monomer residue of the anchor layer, "-" represents a covalent bond, and n is 1 or 2. Preferably, n=1.
[0135] The anchor layer has a thickness of 1 to 5 nm, preferably 1.2 to 2 nm.
[0136] The dispersity of the spherical nanostructures is less than 1.35, preferably less than 1.25.
[0137] Method for producing primed nanostructures The method of producing primed nanostructures from precursor nanostructures is shown in schematic form in Figure 3. To produce primed nanostructures with a particular particle size and particle size distribution in a quality suitable for large scale production, certain process conditions must be met, as described in more detail below. It is envisioned to mix two, three or several different monomers, in any combination of chemically compatible monomers, either by mixing the monomers prior to polymerization or by grafting one polymer onto another.
[0138] The method for obtaining the nanostructures of the present disclosure includes mixing the precursor nanostructures in solution with the monomer precursor of the anchor layer at a temperature between 20° C. and 150° C. for an extended period of time such as 1 to 24 hours or 2 to 6 hours (steps 003 and 004 in FIG. 3).
[0139] The solvent mixture is water and a water-miscible organic solvent. Preferably, the solvent is a lower alcohol such as ethylene glycol, propylene glycol, or a diol such as 1,3-propanediol. In particular, a ratio of water / ethylene glycol of 2:8 to 1:9 is particularly preferred. A mixture of water and two or more water-miscible solvents may be used.
[0140] Heating may be carried out in a sealed pressure vessel or at atmospheric pressure. If heating is carried out at atmospheric pressure, appropriate measures to minimize evaporation of volatile components of the reaction mixture, such as the use of efficient cooling pipes, are advantageous.
[0141] To achieve a desired thickness of the anchor layer, a specific starting concentration of silane monomer according to formula (III) needs to be combined with a specific concentration of precursor nanostructure. Table 1 in Example 11 provides sufficient data for one skilled in the art to produce high quality primed nanostructures with a given thickness of anchor layer, between 0.6 and 2.5 nm, for precursor nanostructures between 12.5 and 23 nm. According to the present disclosure, the ratio of monomer residues of precursor nanostructures to monomer according to formula (III) is between 1:0.5 and 1:20. Preferably, the ratio is between 1:1 and 1:10, such as between 1:3 and 3, such as between 1:2.5 and 1:7.
[0142] The thickness of the anchor layer depends on both the particle size of the precursor nanostructures and the amount of anchor layer precursor monomer. The particle size of the precursor nanostructures depends on the number of monomer residues that make up the precursor nanostructures. For a given ratio of the number of monomer residues in the precursor nanostructure solution to the amount of anchor layer precursor monomer according to formula (III), the resulting anchor layer will be thicker for larger precursor nanostructures.
[0143] In one embodiment of the method, a mixture of 5-25% (volume / volume) water in a lower alcohol is used to dissolve the precursor nanostructures. Preferably, a mixture of 5-25% (volume / volume) water in ethanol, 1- or 2-propanol, or 1,2- or 1,3-propanediol, or ethylene glycol is used to dissolve the precursor nanostructures. Even more preferably, a mixture of 5-25% (volume / volume) water and ethylene glycol is used to dissolve the precursor nanostructures.
[0144] The mixture is heated to a temperature of 20° C. to 150° C. for a period of 1 to 24 hours. It has been found advantageous to use temperatures above room temperature in this process, such as temperatures of 80° C. to 150° C., in order to cause the reaction to proceed at a practical rate.
[0145] In one embodiment, the mixture is heated to a temperature of 90-120° C. for a period of 2-6 hours.
[0146] In another embodiment, the process conditions are a temperature of 95-105° C. and a duration of 3-5 hours.
[0147] In a further embodiment, the mixture is heated to a temperature of 100° C. for a period of 4 hours.
[0148] The anchor layer precursor monomer may be immiscible with the precursor nanostructure solution, in which case the mixture is heated with stirring until a homogenous solution is formed.
[0149] The anchor layer precursor monomer may be finely dispersed in the precursor nanostructure solution by stirring. In such a case, when the anchor layer precursor monomer is finely dispersed in the precursor nanostructure solution, the mixture becomes homogenous before the process is completed. When the anchor layer precursor is finely dispersed in the precursor nanostructure solution and the temperature of the precursor nanostructure solution is higher than room temperature, the mixture often becomes homogenous quickly, such as within 60 minutes, or within 30 minutes, or within 15 minutes, or within 10 minutes.
[0150] In one embodiment, the solution obtained from this process is further treated by filtration.
[0151] Monomer for the anchor layer The silanes used to form the anchor layer have a general structure according to formula (III): TIFF2025513683000013.tif9170, R 1 , R 2 , R 3 , R4 , R 5 , and R 6 is independently selected from the group consisting of lower alkyl and aryl, "-" represents a covalent bond, and n is 1 or 2.
[0152] The reactivity of the trialkoxysilane in the above monomer for polymerization is R 1~6 Varies depending on the type of group. Methyl and ethyl, especially the latter, have been found to be particularly suitable for obtaining the structures of the present disclosure. However, it is also envisaged to use any other lower alkyl group or aryl. Alternatively, the alkoxy group may be modified to a silylamide, acyl, silyl fluoride, or silyl chloride (outside the scope of the present disclosure).
[0153] In one embodiment, R in formula (III) 1 , R 2 , R 3 , R 4 , R 5 , and R 6 are independently a methyl group or an ethyl group, and n=1.
[0154] In certain embodiments, R in formula (III) 1 , R 2 , R 3 , R 4 , R 5 , and R 6 is an ethyl group and n=1.
[0155] In another particular embodiment, R in formula (III) 1 , R 2 , R 3 , R 4 , R 5 , and R 6 is a methyl group and n=1.
[0156] In one embodiment, R in formula (III) 1 , R 2 , R 3 , R 4 , R 5 , and R 6is an isopropyl group, and n=1.
[0157] In another embodiment, R in formula (III) 1 , R 2 , R 3 , R 4 , R 5 , and R 6 is an ethyl group and n=2.
[0158] In yet another embodiment, R in formula (III) 1 , R 2 , R 3 , R 4 , R 5 , and R 6 is a methyl group and n=2.
[0159] In one embodiment, R in formula (III) 1 , R 2 , R 3 , R 4 , R 5 , and R 6 is an isopropyl group, and n=2.
[0160] The precursor nanostructure, the central portion, ie the precursor nanostructure, comprises a polymeric backbone of monomer residues according to formula (II), as described above.
[0161] Method for producing precursor nanostructures and subsequent priming - Patents.com Primed spherical nanostructures can be produced by a process that includes forming precursor nanostructures and then contacting the resulting precursor nanostructures with the anchor layer precursor described above, the process being generally shown in FIG.
[0162] The precursor nanostructures are formed by hydrolytic polymerization of disilane according to formula (IV): TIFF2025513683000014.tif9170, R 7 is independently selected from the group consisting of a negative charge, H, lower alkyl, and aryl; R 8is independently selected from the group consisting of lower alkyl or aryl, and m is an integer from 1 to 5. The resulting precursor nanostructure is contacted with a precursor monomer of the anchor layer under the conditions described above, thereby forming an anchor layer, which is also covalently linked to the central portion (the precursor nanostructure).
[0163] The hydrodynamic diameter of the precursor nanostructure is in the range of 10-90 nm, such as 10-30 nm, such as 15-20 nm.
[0164] Primed spherical nanostructures (i.e., nanostructures having an anchor layer) can be formed, without any intermediate processing steps, by contacting a solution of the precursor nanostructures with the primer precursor in the same vessel in which the precursor nanostructures are synthesized.
[0165] The solution of precursor nanostructures may be further processed before contacting with the anchor layer precursor. The solution of precursor nanostructures may be further processed, for example, by filtration before contacting with the anchor layer precursor. Alternatively, the solution of precursor nanostructures may be further processed by filtration and solvent exchange before contacting with the anchor layer precursor. The solution of precursor nanostructures may be further processed by chromatography before contacting with the anchor layer precursor.
[0166] In one embodiment, R in formula (III) 1 , R 2 , R 3 , R 4 , R 5 , and R 6 is an ethyl group and n=1.
[0167] In one embodiment, R in formula (III) 1 , R 2 , R 3 , R 4 , R 5 , and R 6 is an ethyl group, n=1, and the precursor nanostructure was synthesized from a precursor according to formula (IV): TIFF2025513683000015.tif9170, R 7 and R 8 is independently selected from the group consisting of lower alkyl, substituted and unsubstituted aryl, and m is an integer from 1 to 5.
[0168] In one embodiment, R in formula (III) 1 , R 2 , R 3 , R 4 , R 5 , and R 6 is an ethyl group, n=1, and the precursor nanostructures were synthesized from a precursor comprising 1,7-bis(triethoxysilyl)-4,4-bis(dimethoxyphosphonato)heptane.
[0169] In one embodiment, R in formula (III) 1 , R 2 , R 3 , R 4 , R 5 , and R 6 is an ethyl group, n=1, and the precursor nanostructure comprises a monomer residue according to formula (IV): {(OR 7 )2PO}2-(C){(CH2) m Si(OR 8 )3}2(IV) In the formula, each R 7 is independently selected from the group consisting of a negative charge and H; R 8 At least three of the groups represent bonds to the polymer backbone, and the remaining R 8 The groups are independently selected from the group consisting of a negative charge and H, and m is an integer from 1 to 5.
[0170] In one embodiment, R in formula (III) 1 , R 2 , R 3 , R 4 , R 5 , and R 6 is an ethyl group, n=1, and the precursor nanostructure comprises a monomer residue according to formula (IV): TIFF2025513683000016.tif9170 In the formula, each R 7 is independently selected from the group consisting of a negative charge and H; R 8 At least three of the groups represent bonds to the polymer backbone, and the remaining R 8 The groups are independently selected from the group consisting of a negative charge and H, and m=3.
[0171] In one embodiment, precursor nanostructures are synthesized from precursor monomers comprising 1,7-bis(triethoxysilyl)-4,4-bis(dimethoxyphosphonato)heptane by heating the precursor monomers in a mixture of lower alcohol and water until the precursor nanostructures form, and primed spherical nanostructures are formed by contacting the resulting solution with bis(triethoxysilyl)methane at 90° C.-120° C. for 2 hours-6 hours.
[0172] In one embodiment, precursor nanostructures are synthesized from precursor monomers including 1,7-bis(triethoxysilyl)-4,4-bis(dimethoxyphosphonato)heptane by refluxing the precursor monomers in aqueous ethylene glycol to form the precursor nanostructures, and primed spherical nanostructures are formed by contacting the resulting solution with 2.5 equivalents (relative to 1,7-bis(triethoxysilyl)-4,4-bis(dimethoxyphosphonato)heptane) of bis(triethoxysilyl)methane at 95° C.-105° C. for 3 hours-5 hours.
[0173] In one embodiment, the precursor nanostructures have a hydrodynamic diameter of 15 nm to 20 nm and are synthesized from precursor monomers including 1,7-bis(triethoxysilyl)-4,4-bis(dimethoxyphosphonato)heptane by refluxing the precursor monomers in 90% (vol / vol) aqueous ethylene glycol for 48 hours to give the precursor nanostructures, and the primed spherical nanostructures are formed by contacting the resulting solution with 2.5 equivalents (relative to 1,7-bis(triethoxysilyl)-4,4-bis(dimethoxyphosphonato)heptane) of bis(triethoxysilyl)methane at 100° C. for 4 hours to obtain an anchor layer with a thickness of 1 nm to 2 nm.
[0174] In one embodiment, precursor nanostructures are synthesized from precursor monomers comprising 1,7-bis(triethoxysilyl)-4,4-bis(dimethoxyphosphonato)heptane by heating the precursor monomers in a mixture of lower alcohol and water until the precursor nanostructures form, and primed spherical nanostructures are formed by contacting the resulting solution with 1,2-bis(triethoxysilyl)ethane at 90° C.-120° C. for 2 hours-6 hours.
[0175] Use of Primed Nanostructures as Precursors for Coated Nanostructures Primed nanostructures according to the present disclosure can be used as precursors to other materials suitable for a variety of applications.
[0176] One such use is as a precursor to coated nanostructures, which may be for in vivo use.
[0177] Thus, the nanostructures of the present disclosure can be further derivatized to make them suitable for use in vivo. Typically, the primed nanostructures are modified to include a coating. Preferably, the coating includes hydrophilic groups, thereby making the nanostructures more biocompatible. In a specific embodiment, the coating includes polyethylene glycol.
[0178] The coated nanostructures are suitable as nanocarriers for radionuclide imaging and / or therapy.
[0179] The coated nanostructures may be used as intravenous imaging and / or radiotherapy agents. In such applications, the average hydrodynamic diameter of the final coated nanostructures is 15-100 nm, preferably 20-50 nm, and most preferably 25-35 nm. The hydrodynamic diameter of the final coated nanostructures is shown in Figure 2c as D C is equivalent to.
[0180] Pharmaceutical Compositions The present disclosure also relates to a pharmaceutical composition comprising a plurality of spherical nanostructures according to the present disclosure, preferably the spherical nanostructures further comprising a coating. Such pharmaceutical compositions are preferably prepared as a solution, preferably as an aqueous solution.
[0181] In one embodiment, the pharmaceutical composition further comprises one or more excipients, such as an antioxidant and / or a buffering agent.
[0182] The pharmaceutical composition may be used as is. Alternatively, the nanostructures in the pharmaceutical composition chelate a metal. In certain cases, the nanostructures in the pharmaceutical composition chelate a radioisotope.
[0183] Typically, when used in cancer treatment and / or imaging, the spherical nanostructures further comprise a radioisotope. Depending on the application, different radioisotopes are used.
[0184] The compositions may include nanostructures that include a single radioisotope or two or more different types of radioisotopes. Radioisotopes, also referred to as radionuclides, suitable for various applications are listed above.
[0185] In one embodiment, the pharmaceutical composition is used for imaging.
[0186] Pharmaceutical compositions according to the present disclosure used for SPECT imaging typically contain gallium-67 ( 67 Ga), Indium-111 ( 111 In), Technetium-99m ( 99m Tc 3+ ), Lutetium-177( 177 Lu), and / or Thallium-201 ( 201 Tl).
[0187] Pharmaceutical compositions according to the present disclosure used for PET imaging typically contain copper-62 ( 62 Cu), Gallium-68( 68 Ga), Rubidium-82( 82 Rb), Yttrium-86( 86 Y), and / or Zirconium-89 ( 89 Zr).
[0188] Pharmaceutical compositions according to the present disclosure are used for radionuclide therapy, typically Actinium-225 ( 225 Ac), Copper-64( 64 Cu), Copper-67( 67 Cu), Holmium-166( 166 Ho), lead-212( 212 Pb), Lutetium-177( 177 Lu), Radium-223 ( 223 Ra), Rhenium-186( 186 Re), rhenium-188( 188 Re), Samarium-153( 153 Sm), Strontium-89 ( 89 Sr), Thorium-227( 227 Th), and / or Yttrium-90 (90 Y).
[0189] In one embodiment, the pharmaceutical composition is used for radionuclide therapy of metastatic cancer.
[0190] The pharmaceutical composition may be used to prepare a pharmaceutical composition comprising nanostructures that include a radioisotope. Such pharmaceutical compositions are prepared by contacting a solution of the nanostructures with a solution that includes a radionuclide. Preferably, the nanostructures include a coating, preferably a coating that includes a polyethylene glycol moiety.
[0191] Pharmaceutical compositions containing one or more chelated radioisotopes can be prepared by contacting a solution of the nanostructures with a solution containing the radionuclide at or near the point of use.
[0192] Alternatively, a pharmaceutical composition comprising one or more chelated radioisotopes is prepared by contacting a solution of nanostructures with a solution comprising a radionuclide at a location separated by some distance from the point of use, and the pharmaceutical composition comprising one or more chelated radioisotopes is transported to the point of use very quickly, such as within one month, such as within two weeks, such as within one week, such as within three days, such as within one day. EXAMPLES
[0193] General experimental conditions Materials, reagents, and solvents were obtained from commercial sources and used without further purification unless otherwise noted. Solvents were of reagent grade or similar unless otherwise noted.
[0194] 1,7-Bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane was prepared according to published procedures (WO2013041623A1, Example 3).
[0195] DLS was measured using a Malvern Instruments Zetasizer Nano ZEN3600 and processed using the general process settings in the Zetasizer software.
[0196] The term "PES" is an acronym for polyethersulfone.
[0197] The term "GF / A Filter" is an abbreviation for Glass Microfiber Filter, Grade GF / A.
[0198] The term "RPM" is an acronym for Revolutions Per Minute.
[0199] Example 1. Adding an anchor layer to a precursor nanostructure to form a primed nanostructure Example 1A. Formation of Primed Nanostructures by Large-Scale Addition of Anchor Layers to Precursor Nanostructures Using Bis(triethoxysilyl)methane (BTESM) as Anchor Layer Precursor A 5 liter jacketed reactor equipped with a mechanical stirrer, temperature probe, and connection to a vacuum-nitrogen manifold was charged with 4338 g of a solution of precursor nanostructures with an average diameter of 17.6 nm and a phosphorus concentration of 70 mM, formed by refluxing 93.60 g of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane in 4501 g of 90.0% (volume / volume) aqueous ethylene glycol for 48 hours. The mantle temperature was set to 100° C., and when the internal temperature exceeded 99° C., 116.48 g of bis(triethoxysilyl)methane was added. The mixture was stirred at 300 RPM for 5 minutes, after which the mixture became homogenous and the stirring speed was reduced to 150 RPM. Heating was continued for 4 hours, after which the solution was cooled to ambient temperature and filtered through a double glass fiber filter.
[0200] Average diameter (DLS)=19.7nm, [P](ICP-OES)=64mM, [Si](ICP-OES)=225mM
[0201] Therefore, the thickness of the anchor layer was 1.05 nm.
[0202] Example 1B. Formation of Primed Nanostructures by Small Scale Addition of Anchor Layers to Precursor Nanostructures Using Bis(triethoxysilyl)methane (BTESM) as Anchor Layer Precursor A 20 ml reaction vial equipped with a magnetic stir bar was charged with 10 ml of a solution of precursor nanostructures with an average diameter of 17.5 nm and a phosphorus concentration of 136 mM, formed by heating 7.91 g of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane in 146 ml of ethylene glycol and 36.5 ml of water at 125° C. for 264 hours. The vial was heated in a preheated 100° C. oil bath for 15 minutes, after which 553 mg of bis(triethoxysilyl)methane (1.63 mmol, 2.5 equivalents relative to the nominal amount of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane in the solution) was added. The mixture was stirred vigorously for 10 minutes, after which the solution became homogenous and the stirring speed was reduced. After 4 hours of heating, the vial was removed from the oil bath.
[0203] Average diameter (DLS)=20.5nm, [P](ICP-OES)=125mM, [Si](ICP-OES)=488mM
[0204] Therefore, the thickness of the anchor layer was 1.5 nm.
[0205] Example 1C. Formation of Primed Nanostructures by Small Scale Addition of Anchor Layers to Precursor Nanostructures Using 1,2-Bis(triethoxysilyl)ethane (BTESE) as Anchor Layer Precursor A 25 ml round bottom flask equipped with a magnetic stir bar was charged with 10 ml of a solution of precursor nanostructures with an average diameter of 16.2 nm and a phosphorus concentration of 71 mM, formed by heating 5.82 g of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane in 250 ml of 90.0% (volume / volume) aqueous ethylene glycol at reflux (140° C.) for 90 hours. The flask was heated in a preheated 100° C. oil bath for 10 minutes, after which 315 mg of 1,2-bis(triethoxysilyl)ethane (0.88 mmol, 2.5 equivalents relative to 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane) was added. The mixture was stirred vigorously for 15 minutes, after which the solution became homogenous and the stirring rate was reduced. After 4 hours of heating, the flask was removed from the oil bath.
[0206] Average diameter (DLS)=19.0nm
[0207] Therefore, the thickness of the anchor layer was 1.4 nm.
[0208] Example 2. Addition of an insufficiently thick anchor layer to precursor nanostructures - an example outside the scope of this disclosure A 20 ml reaction vial equipped with a magnetic stir bar was charged with 10 ml of a solution of precursor nanostructures with an average diameter of 19.1 nm and a phosphorus concentration of 130 mM, formed by heating 5.74 g of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane in 105 ml of ethylene glycol and 26 ml of water to 125° C. for 285 hours. The vial was heated in a preheated 100° C. oil bath for 10 minutes, after which 223 mg of 1,2-bis(triethoxysilyl)methane (0.65 mmol, 1 equivalent relative to the nominal amount of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane in the solution) was added. The mixture was stirred vigorously for 5 minutes, after which the solution became homogenous and the stirring speed was reduced. After 4 hours of heating, the vial was removed from the oil bath.
[0209] Average diameter (DLS)=20.2nm
[0210] The thickness of the added anchor layer was therefore 0.55 nm.
[0211] Example 3. Examples of inappropriate primer precursors - examples outside the scope of this disclosure Example 3A. Adding a Silica Layer to a Precursor to Form Primed Nanostructures with an Anchor Layer Formed from Tetraethylorthosilicate - Reference Example Outside the Scope of This Disclosure A 20 ml reaction vial equipped with a magnetic stir bar was charged with 10 ml of a solution of precursor nanostructures with an average diameter of 19.1 nm and a phosphorus concentration of 130 mM, formed by heating 5.74 g of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane in 105 ml of ethylene glycol and 26 ml of water at 125° C. for 285 hours. The vial was heated in a preheated 100° C. oil bath for 5 minutes, after which 673 mg of tetraethyl orthosilicate (3.23 mmol, 5 equivalents relative to the nominal amount of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane) was added. After vigorously stirring the mixture for 10 minutes, the solution became homogenous and the stirring speed was reduced. After 4 hours of heating, the vial was removed from the oil bath. Average diameter (DLS)=21.5 nm. Therefore, the thickness of the anchor layer was 1.2 nm.
[0212] Example 3B. 1,6-Bis(trimethoxysilyl)hexane does not form an anchor layer - a reference example outside the scope of this disclosure A 25 ml round bottom flask equipped with a magnetic stir bar was charged with 10 ml of a solution of precursor nanostructures with an average diameter of 16.2 nm and a phosphorus concentration of 71 mM, formed by heating 5.82 g of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane in 250 ml of 90.0% (volume / volume) aqueous ethylene glycol at reflux (140° C.) for 90 hours. The flask was heated in a preheated 100° C. oil bath for 15 minutes, after which 290 mg of 1,6-bis(trimethoxysilyl)hexane (0.89 mmol, 2.5 equivalents relative to the nominal amount of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane) was added. The mixture was stirred vigorously for 10 minutes, after which the solution became homogeneous and the stirring speed was reduced. Samples were taken for analysis after 30 min, 1 h, 2 h, and 3 h. Aliquots of samples diluted with water for DLS measurements could only be filtered through a 0.2 μm syringe filter with strong force. DLS measurements of the filtered samples showed no nanostructures within the 5-150 nm range, indicating that the precursor nanostructures were essentially completely aggregated.
[0213] Example 4. Adding a coating layer to a primed nanostructure to form a coated nanostructure A two-neck round-bottom flask fitted with a reflux condenser at the vertical end connected at its top to a vacuum-nitrogen manifold and with a septum-stopped side end was charged with 5 mL of a solution of primed nanostructures (mean diameter (DLS) = 22.2 nm; nominal [P] = 130 mM; 0.65 mmol P; anchor layer thickness = 1.5 nm) prepared as in Example 1B. The nanostructure solution was degassed and lowered into a preheated 110 °C oil bath. After 10 minutes, a 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy)silyl)-4,4-bis(ω-methyl-(ethyleneoxy)silyl) in anhydrous dioxane heated to 40 °C was added. 45 400 μl of a 50% (weight / weight) solution of 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45An additional 2.7 ml of the 3-methyl)heptane solution was added via syringe pump at a rate of 142 μl / hr. After a total of 48 hours, the solution was allowed to cool to ambient temperature. The solution was diluted to 25 ml with water and filtered through a 0.2 μm PES syringe filter. The resulting solution was diluted to 800 ml with water and concentrated to approximately 20 ml using a tangential flow filtration device with a nominal cutoff of 300 kD. The dilution-concentration procedure was repeated a total of three times, after which the solution was further concentrated to 7 ml with a spin filter with a nominal cutoff of 300 kD.
[0214] Average diameter (DLS)=29.6nm, [P](ICP-OES)=75mM, [Si](ICP-OES)=281mM
[0215] Nanostructures prepared in this manner did not precipitate even when exposed to a 20 mM CaCl2 solution, a factor indicating compatibility with biological fluids.
[0216] Example 5. Addition of a coating layer to a primed nanostructure having an insufficiently thick primer layer (anchor layer) - a reference example outside the scope of this disclosure A two-neck round-bottom flask fitted with a reflux condenser at the vertical neck connected at its top to a vacuum-nitrogen manifold and with the side neck plugged with a septum was charged with 4 ml of a solution of primed nanostructures prepared from Example 2 (mean diameter (DLS) = 20.2 nm; nominal [P] = 130 mM; 0.52 mmol P; anchor layer thickness = 0.55 nm). The nanostructure solution was degassed and lowered into a preheated 110°C oil bath. After 10 minutes, 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy)silyl)-4,4-bis(ω-methyl-(ethyleneoxy)silyl) in anhydrous dioxane heated to 40°C was added. 45 300 μl of a 50% (weight / weight) solution of 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45An additional 1.9 ml of the 3-methyl)heptane solution was added via syringe pump at a rate of 100 μl / hr. After a total of 48 hours, the solution was allowed to cool to ambient temperature. The solution was diluted to 20 ml with water and filtered through a 0.2 μm PES syringe filter. The resulting solution was diluted to 800 ml with water and concentrated to approximately 20 ml using a tangential flow filtration device with a nominal cutoff of 300 kD. The dilution-concentration procedure was repeated a total of three times, after which the solution was further concentrated to 6.5 ml with a spin filter with a nominal cutoff of 300 kD.
[0217] Average diameter (DLS)=28.8nm, [P](ICP-OES)=76mM, [Si](ICP-OES)=175mM
[0218] Although the nanostructures prepared in this manner do not precipitate when exposed to 20 mM CaCl2 solution, they still exhibit short plasma half-lives and poor in vivo performance, as shown in Example 9.
[0219] Example 6. Adding a coating layer to a silica-primed nanostructure with an anchor layer formed from tetraethylorthosilicate - a reference example outside the scope of this disclosure A two-neck round-bottom flask fitted with a reflux condenser at the vertical neck connected at its top to a vacuum-nitrogen manifold and with a septum-stopped side neck was charged with 5 mL of a solution of primed nanostructures (mean diameter (DLS) = 21.5 nm; nominal [P] = 130 mM; 0.65 mmol P) prepared according to Example 3A. The nanostructure solution was degassed and lowered into a preheated 110°C oil bath. After 5 minutes, 400 μL of a 50% (wt / wt) solution of 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy)45-methyl)heptane in anhydrous dioxane heated to 40°C was added. An additional 2.7 ml of the warm 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy)45-methyl)heptane solution was added via syringe pump at a rate of 142 μl / hr. After a total of 48 hours, the solution was allowed to cool to ambient temperature. The solution was diluted to 25 ml with water and filtered through a 0.2 μm PES syringe filter. The resulting solution was diluted to 800 ml with water and concentrated to approximately 20 ml using a tangential flow filtration apparatus with a nominal cutoff of 300 kD. The dilution-concentration procedure was repeated a total of three times, after which the solution was further concentrated to 6 ml with a spin filter with a nominal cutoff of 300 kD.
[0220] Average diameter (DLS)=29.4nm, [P](ICP-OES)=83mM, [Si](ICP-OES)=325mM
[0221] Nanostructures prepared in this manner do not precipitate when exposed to a 20 mM CaCl2 solution, but do exhibit low hydrolytic stability, as shown in Example 8.
[0222] Example 7. Addition of a coating layer to unprimed nanostructures - an example outside the scope of this disclosure A two-necked round-bottom flask fitted with a reflux condenser at the vertical neck connected at the top to a vacuum-nitrogen manifold and with a septum-stopped side neck was charged with 5 ml of a solution of unprimed precursor nanostructures with an average diameter of 19.1 nm and a phosphorus concentration of 130 mM, formed by heating 5.74 g of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane in 105 ml of ethylene glycol and 26 ml of water at 125° C. for 285 hours. The nanostructure solution was degassed and lowered into a preheated 110° C. oil bath. After 5 minutes, 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45 400 μl of a 50% (weight / weight) solution of 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy) 45 An additional 2.7 ml of the 3-methyl)heptane solution was added via syringe pump at a rate of 142 μl / hr. After a total of 48 hours, the solution was allowed to cool to ambient temperature. The solution was diluted to 25 ml with water and filtered through a 0.2 μm PES syringe filter. The resulting solution was diluted to 800 ml with water and concentrated to approximately 20 ml using a tangential flow filtration device with a nominal cutoff of 300 kD. The dilution-concentration procedure was repeated a total of three times, after which the solution was further concentrated to 6 ml with a spin filter with a nominal cutoff of 300 kD.
[0223] Average diameter (DLS)=29.0nm, [P](ICP-OES)=80mM, [Si](ICP-OES)=107mM
[0224] Nanostructures prepared in this manner precipitated when exposed to a physiologically relevant 2 mM CaCl2 solution, demonstrating the reduced suspension stability of coated nanostructures without an anchor layer compared to coated nanostructures including an anchor layer according to the present disclosure (Example 4).
[0225] Example 8. Comparison of hydrolytic stability A 1.25 ml sample of the nanostructure solution from Example 4 (nanostructures with anchor layers derived from BTESM) was diluted to 4 ml with water. To this solution, 204 μl of a 19.7 mM aqueous solution of LuCl3 was added, the solution was heated to 60° C., and then 1.26 ml of 1 M Tris buffer at pH 7.7 was added. Heating was continued for 2 hours, and the resulting solution was filtered through a 0.2 μm syringe filter.
[0226] A sample of the nanostructure solution from Example 6 (nanostructures with an anchor layer formed from tetraethylorthosilicate - a reference example outside the scope of this disclosure) was treated with LuCl3 in the same manner.
[0227] Samples of these solutions were then subjected to constant volume tangential flow filtration in 75 mmol Tris buffer at pH 7.4 using a filter with a nominal cutoff of 50 kD for 20 hours, and the retentate was analyzed for [Si] and [P] by ICP-OES. The ratio of [Si] / [P] decreased from 3.71 to 3.66 (-1%) for the nanostructure solution from Example 4, and from 3.74 to 3.23 (-14%) for the nanostructures from Example 6. This demonstrates the increased hydrolytic stability of the nanostructures having an anchor layer according to the present disclosure (Example 4) compared to the nanostructures having an anchor layer formed from tetraethyl orthosilicate (Example 6).
[0228] Example 9. Comparison of in vivo stability Solutions of nanostructures from Example 4 (nanostructures with anchor layer (thickness 1.5 nm) derived from BTESM), Example 5 (nanostructures with anchor layer of insufficient thickness (0.55 nm) - example outside the scope of this disclosure) and Example 6 (nanostructures with anchor layer formed from tetraethyl orthosilicate - example outside the scope of this disclosure) loaded with lutetium (LuCl) as in Example 8 were further formulated for injection by adding CaCl, HCl and mannitol to obtain an injection solution with pH=7.4, [P]=9-11 mM, and [Lu]=0.40 mM and an osmolality suitable for injection.
[0229] In vivo behavior was investigated by injecting the test article into female BALB / c mice at a dose of 2 μmol Lu / kg. Blood was collected 1, 6, and 24 hours after injection, and plasma was analyzed for [Lu] and [Si] by ICP-OES.
[0230] Plasma t of nanostructures calculated from the concentration of Lu 1 / 2 The plasma half-life was beneficially long at 12 hours for the nanostructure from Example 4 (anchor layer thickness = 1.5 nm), 5 hours for the nanostructure from Example 5 (anchor layer thickness = 0.55 nm), and 4 hours for the nanostructure from Example 6 (having an anchor layer formed from tetraethylorthosilicate), demonstrating that if the anchor layer is sufficiently thick, nanostructures having an anchor layer according to the present disclosure can have extended plasma half-lives in vivo, as demonstrated here for an anchor layer derived from BTESM.
[0231] t 1 / 2 Calculating from the Si concentration, the results are again 12 hours for the nanostructures from Example 4 (having an anchor layer according to the present disclosure), but only 5 hours for the nanostructures from Example 5, and 3 hours for the nanostructures from Example 6, demonstrating the higher hydrolytic stability of the nanostructures having an anchor layer according to the present disclosure, here demonstrated in vivo for an anchor layer derived from BTESM.
[0232] Example 10. NMR of primed nanostructures A sample of precursor nanostructures similar to that used in Example 1B, and a sample of primed nanostructures similar to the product from Example 1B, were transferred to DO by first exchanging the solvent into water using repeated dilution-concentration cycles in a spin filter with a nominal cutoff of 100 kD, and then exchanging the water into DO in the same manner.
[0233] The 1H-NMR spectrum was recorded and is shown in Figure 4. The top spectrum is of the precursor nanostructures, which has been shifted from the spectrum of the primed nanostructures for clarity. The inset is a zoomed-in view of the same spectrum, showing prominent features in the region around 0 ppm.
[0234] The main peak of the precursor nanostructures is very broad, peaking at approximately 25 ppm (12,500 Hz), due to the high degree of crosslinking of the precursor nanostructures. The spectrum of the primed nanostructures shows essentially the same features, except for a smaller but similarly broad peak centered at 0.25 ppm, which corresponds to the methylene moieties of the anchor layer. This demonstrates the high degree of crosslinking of the anchor layer.
[0235] Example 11. Synthesis of nanostructures with different particle sizes and anchor layer thicknesses Precursor nanostructures of various particle sizes, synthesized in a similar manner to the precursor nanostructures of Examples 1A and 1B, were treated with BTESM as in Example 1B, but with varying amounts of BTESM according to Table 1. The diameters of the primed nanostructures were evaluated by DLS. As can be seen from Table 1, many combinations of cores (precursor nanostructures) and anchor layers can be achieved in a predictable manner. TIFF2025513683000017.tif149170
[0236] Example 12. Calculation of density and cross-linking degree of anchor layer A sample of primed nanostructures prepared as in Example 1A and a sample of precursor nanostructures similar to those used in Example 1A were dried to a powder by first solvent-exchanging into water and then freeze-drying the resulting solution using a procedure similar to that used in Example 10.
[0237] The density of the resulting powders was determined by constraining it between the density of a mixture of heptane and dibromomethane such that the powders settle only slightly when centrifuged and the density of a mixture of heptane and dibromomethane such that the powders float only slightly when centrifuged. The densities were found to be 1.739 g / ml and 1.649 g / ml for the primed and precursor nanostructures, respectively. The density of the anchor layer was calculated to be 1.9 g / ml (1.82-2.35 g / ml) assuming a core-shell model (see FIG. 2B) and spherical nanostructures.
[0238] This indicates an average crosslinking degree of approximately 4 bonds per monomer residue into the polymer network.
[0239] Example 13. Formation of Primed Nanostructures by Addition of an Anchor Layer to a Precursor Nanostructure Using 1,2-Bis(triethoxysilyl)ethane (BTESE) as the Anchor Layer Precursor A 15 ml reaction vial equipped with a magnetic stir bar was charged with 5 ml of the same precursor nanostructure (mean diameter 17.6 nm, phosphorus concentration 70 mM) solution used in Example 1A. The vial was heated in a preheated 100° C. oil bath for 15 min, after which 155 mg of 1,2-bis(triethoxysilyl)ethane (0.44 mmol, 2.5 equivalents relative to the nominal amount of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane in the solution) was added. The mixture was stirred vigorously for 10 min, after which the solution became homogenous and the stirring speed was reduced. After 4 h of heating, the vial was removed from the oil bath.
[0240] Average diameter (DLS)=20.3nm, [P](ICP-OES)=60mM, [Si](ICP-OES)=218mM
[0241] Therefore, the thickness of the anchor layer was 1.3 nm.
[0242] Example 14. Adding a coating layer to a nanostructure primed with 1,2-bis(triethoxysilyl)ethane (BTESE) to form a coated nanostructure The nanostructures from Example 13 primed with 1,2-bis(triethoxysilyl)ethane were coated with 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy)45-methyl)heptane using a procedure similar to that of Example 4.
[0243] Average diameter (DLS)=26.4nm, [P](ICP-OES)=15.9mM, [Si](ICP-OES)=59mM
[0244] Example 15. Adding an anchor layer to a precursor nanostructure to form a primed nanostructure using 1,3-bis(triethoxysilyl)propane (n=3 in formula I) as the anchor layer precursor - a reference example outside the scope of this disclosure A 15 ml reaction vial equipped with a magnetic stir bar was charged with 5 ml of the same precursor nanostructure (mean diameter 17.6 nm, phosphorus concentration 70 mM) solution used in Example 1A. The vial was heated in a preheated 100° C. oil bath for 13 minutes, after which 161 mg of 1,3-bis(triethoxysilyl)propane (0.44 mmol, 2.5 equivalents relative to the nominal amount of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane in the solution) was added. The mixture was stirred vigorously for 20 minutes, after which the solution became homogenous and the stirring speed was reduced. After 4 hours of heating, the vial was removed from the oil bath.
[0245] Repeated attempts to measure particle size by DLS did not yield reproducible results, and the thickness of the anchor layer could not be determined. [P](ICP-OES) = 65 mM, [Si](ICP-OES) = 222 mM
[0246] Example 16. Adding a Coating Layer to Nanostructures Primed with 1,3-Bis(triethoxysilyl)propane (n=3 in Formula I) to Form Coated Nanostructures - Reference Example Outside the Scope of the Disclosure The nanostructures from Example 15 primed with 1,3-bis(triethoxysilyl)propane were coated with 1,7-bis(triethoxysilyl)-4,4-bis(ω-methyl-(ethyleneoxy)45-methyl)heptane using a procedure similar to that of Example 4. The SEC-ELSD profile of the nanostructures prepared in this manner shows a very broad particle size profile that is incompatible with medical applications.
[0247] Average diameter (DLS)=24nm, [P](ICP-OES)=15mM, [Si](ICP-OES)=57mM
[0248] Example 17. Synthesis of Core Nanostructures (i.e., Central Moieties) According to Example 1c of US Patent Application Publication No. 2017 / 0106105 A1 - Reference Example Outside the Scope of the Disclosure The core nanostructure was synthesized similarly to Example 1c of US Patent Application Publication No. 2017 / 0106105(A1). A 150 ml pressure-resistant vial was charged with 3.896 g of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane and 65 ml of ethylene glycol was added. The clear solution was stirred briefly, and then 16 ml of water was added. The cloudy solution was degassed by repeated vacuum-nitrogen cycles, after which the pressure-resistant vial was sealed and heated to 120° C. for 33 hours.
[0249] TIFF2025513683000018.tif8170
[0250] Example 18. Adding a coating layer to an unprimed core nanostructure (i.e., central portion) according to Example 1c of US Patent Application Publication No. 2017 / 0106105(A1) to obtain a coated nanostructure according to Example 2b of US Patent Application Publication No. 2017 / 0106105(A1) - a reference example outside the scope of this disclosure The nanostructures according to Example 17 were coated similarly to Example 2b of US Patent Application Publication No. 2017 / 0106105(A1). After 20 ml of the solution of the nanostructures from Example 17 was degassed by repeated vacuum-nitrogen cycles, the solution was heated in a preheated oil bath at 114° C. for 15 minutes. Methoxy(polyethyleneoxy)propyl]trimethoxysilane (90% purity, 12 ethylene glycol units, 1107 mg) was dissolved in 1.225 ml of ethylene glycol. 1.55 ml of the coating solution of methoxy(polyethyleneoxy)propyl]trimethoxysilane was added to the nanostructures at 150 μl / min. After 6 hours of heating, the solution was cooled, diluted to 100 ml with water, and filtered through a double GF / A glass fiber filter and a 0.2 μm PES filter. The resulting solution was diluted to 800 ml with water and concentrated to approximately 20 ml using a tangential flow filtration device with a nominal cutoff of 300 kD. The dilution-concentration procedure was repeated a total of three times, after which the solution was further concentrated to 20 ml on a spin filter with a nominal cutoff of 300 kD.
[0251] TIFF2025513683000019.tif8170
[0252] Example 19. Preparation of primed and coated core nanostructures synthesized according to Example 1c of US Patent Publication No. 2017 / 0106105 A1 - Reference outside the scope of this disclosure Example 19A. Addition of an anchor layer (primer treatment) to a core nanostructure synthesized according to US Patent Application Publication No. 2017 / 0106105(A1) - Reference outside the scope of this disclosure A 50 ml round bottom flask equipped with a magnetic stir bar was charged with 30 ml of the solution of precursor nanostructures from Example 17 (mean diameter 14.1 nm, phosphorus concentration 138 mM). The flask was heated in a preheated 100° C. oil bath for 10 minutes, after which 1.92 g of 1,2-bis(triethoxysilyl)ethane (BTESM) (5.63 mmol, 2.5 equivalents relative to the nominal amount of 1,7-bis(triethoxysilyl)-4,4-bis(dimethylphosphonato)heptane in the solution) was added. The mixture was stirred vigorously for 30 minutes, after which the solution became homogenous and the stirring speed was reduced. After 4 hours of heating, the flask was removed from the oil bath.
[0253] Average diameter (DLS)=21.3nm, [P](ICP-OES)=60mM, [Si](ICP-OES)=218mM
[0254] Therefore, the thickness of the anchor layer was 3.6 nm.
[0255] Example 19B. Adding a Coating Layer to Nanostructures Synthesized According to US Patent Publication No. 2017 / 0106105(A1) Primed with BTESM to Form Coated Nanostructures - Reference Example Outside the Scope of the Disclosure The primed nanostructures from Example 19A were coated with methoxy[(polyethyleneoxy)propyl]trimethoxysilane (90% purity, 12 ethylene glycol units) using a procedure similar to that of Example 4.
[0256] Average diameter (DLS)=21.1nm, [P](ICP-OES)=9.9mM, [Si](ICP-OES)=36.9mM
[0257] Example 20. Further comparison of hydrolytic stability The coated nanostructures according to Examples 4, 14, 18, and 19B were evaluated in an accelerated aging test.
[0258] Example 4 is a PEG-coated nanostructure having a central portion in accordance with the present disclosure and an anchor layer derived from a BTESM (ie, n=1) in accordance with the present disclosure.
[0259] Example 14 is a PEG-coated nanostructure having a central portion in accordance with the present disclosure and an anchor layer derived from BTESE (ie, n=2) in accordance with the present disclosure.
[0260] Example 18 is a PEG-coated nanostructure with a central portion synthesized according to Example 1c of US Patent Application Publication No. 2017 / 0106105 A1, without the presence of an anchor layer according to the present disclosure.
[0261] Example 19B is a PEG-coated nanostructure having a central portion synthesized according to Example 1c of U.S. Patent Application Publication No. 2017 / 0106105(A1) and an anchor layer derived from a BTESM (i.e., n=1) according to the present disclosure.
[0262] A 500 μl aliquot of each nanostructure solution in a 1.5 ml crimp-cap vial was heated in an oven at 60° C. for 3 days and evaluated by SEC-ELSD. The relative amount of degradation products was determined as the sum of all peaks eluting after the peak corresponding to the nanostructure. TIFF2025513683000020.tif78170
[0263] As can be seen from Table 2, coated nanostructures having anchor layers according to the present disclosure, i.e., according to Examples 4, 14, and 19B, produce significantly fewer molecular degradation products than coated nanostructures without an anchor layer, i.e., according to Example 18.
[0264] Furthermore, the coated nanostructures having a central portion according to the present disclosure and an anchor layer according to the present disclosure (Examples 4 and 14) are more hydrolytically stable than the nanostructure having a central portion synthesized according to Example 1c of U.S. Patent Application Publication No. 2017 / 0106105 A1 and an anchor layer according to the present disclosure (Example 19B).
[0265] Example 21. Hydrodynamic size distribution of several nanostructure samples. Comparison of TIFF2025513683000021.tif6170 with polydispersity index (PDI) Nanostructure samples with different dispersions were analyzed by DLS, and the dispersion of each sample was TIFF2025513683000022.tif7170 and the polydispersity index (PDI) was calculated (shown in Table 3). TIFF2025513683000023.tif105170
[0266] From Table 3, It can be seen that TIFF2025513683000024.tif6170 and PDI are correlated, and that both parameters represent the breadth of the size distribution of the nanostructure population. However, a simple, monotonic conversion between the two does not fit the data. It can be concluded that TIFF2025513683000025.tif5170 and PDI capture different aspects of the shape of the particle size distribution.
Claims
1. A plurality of spherical nanostructures, said plurality of spherical nanostructures having a dispersity between 1 and 1.8, each nanostructure comprising: A central moiety comprising a polymer backbone of monomer residues according to formula (II), During the ceremony, Each R 1 and R 2 is independently selected from the group consisting of a negative charge and H; Each R 3 are independently selected from the group consisting of a negative charge, H, and a covalent bond to the polymer backbone, and at least three R 3 is a bond to the polymer backbone, and m is an integer from 1 to 5, The central portion of the nanostructure has a volume average hydrodynamic diameter of 10 nm to 90 nm. an anchor layer surrounding said central portion, said anchor layer comprising a polymer of monomer residues according to formula (I); During the ceremony, each R is independently selected from the group consisting of a negative charge, H, and a covalent bond, and at least two R are independently selected from the group consisting of a covalent bond to a monomer residue of the core portion and a covalent bond to a monomer residue of the anchor layer; "-" represents a covalent bond, and n is 1 or 2; the anchor layer having a thickness of 1 to 5 nm; A plurality of spherical nanostructures comprising:
2. 10. The nanostructures of claim 1, wherein the anchor layer has a thickness of 1.1 to 2.5 nm, or 1.3 to 1.6 nm.
3. 3. The plurality of nanostructures of claim 1 or 2, wherein 2 to 5 R are selected from the group consisting of covalent bonds to monomer residues of the core portion and covalent bonds to monomer residues of the anchor layer.
4. The plurality of spherical nanostructures according to any one of claims 1 to 3, wherein n is 1.
5. The plurality of spherical nanostructures according to any one of claims 1 to 4, wherein m is 3.
6. The plurality of spherical nanostructures according to any one of claims 1 to 5, wherein the nanostructures further comprise a coating, preferably the coating comprises hydrophilic groups.
7. The plurality of spherical nanostructures of claim 6 , wherein the coating comprises polyethylene glycol.
8. A method for producing a plurality of spherical nanostructures according to any one of claims 1 to 7, comprising the steps of: (1) have a volume average hydrodynamic diameter of 10 nm to 90 nm, each comprising a polymer backbone of monomer residues according to formula (II); During the ceremony, Each R 1 and R 2 is independently selected from the group consisting of a negative charge and H; Each R 3 are independently selected from the group consisting of a negative charge, H, and a covalent bond to the polymer backbone, and at least three R 3 is a bond to the polymer backbone, and m is an integer from 1 to 5; A precursor nanostructure; According to formula (III): During the ceremony, R 1 , R 2 , R 3 , R 4 , R 5 , and R 6 is independently selected from the group consisting of lower alkyl and aryl; "-" represents a covalent bond, and n is 1 or 2; With the monomer, Providing a mixture in a mixture of water and a water-miscible organic solvent, the ratio of monomer residues of the precursor nanostructure to monomers according to formula (III) is from 1:0.5 to 1:20; and (2) heating the mixture of step (1) to a temperature of from 20° C. to 150° C. for a period of from 1 to 24 hours; A manufacturing method comprising:
9. R 1 , R 2 , R 3 , R 4 , R 5 , and R 6 9. The method of claim 8, wherein is independently selected from the group consisting of methyl and ethyl, and n is 1.
10. 10. The method of claim 8 or claim 9, wherein the ratio of monomer residues of the precursor nanostructure to monomer according to formula (III) is from 1:0.5 to 1:7, and / or in step (2), the mixture of step (1) is heated to a temperature of from 80° C. to 150° C. for a period of from 2 to 6 hours.
11. A pharmaceutical composition comprising a plurality of spherical nanostructures according to claim 6 or claim 7.
12. 8. A pharmaceutical composition for use in the treatment and / or imaging of cancer comprising a plurality of spherical nanostructures according to claim 6 or claim 7, said spherical nanostructures further comprising a radioisotope.
13. 11. Use of a plurality of spherical nanostructures according to any one of claims 1 to 7 and / or the product of the method according to any one of claims 8 to 10 as an intermediate in the production of a plurality of coated spherical nanostructures.
14. 13. Use of a plurality of spherical nanostructures according to any one of claims 1 to 7 and / or the product of the method according to any one of claims 8 to 10 as intermediates in the manufacture of a pharmaceutical product.
15. Use of the pharmaceutical composition according to claim 11 as a carrier for a radioisotope.